Effect of nanomolar concentrations of lanthanum on Desmodesmus quadricauda cultivated under environmentally relevant conditions - Ashraf, Nermeen; Vítová, Milada; Cloetens, Peter; Mijovilovich, Ana; Bokhari, Syed Nadeem Hussain; Küpper, Hendrik (Aquatic toxicology, 2021)
Toxicity of lanthanides is generally regarded as low, and they even have been suggested to be beneficial at low concentrations. This research was conducted to investigate effects of Lanthanum (La) on Desmodesmus quadricauda, a freshwater green microalga. The algal cultures were treated with nanomolar La concentrations under controlled environmentally relevant conditions. Intracellular localization of La was analyzed with μXRF tomography in frozen-hydrated samples. At sublethal concentration (128 nM) La was in hotspots inside the cells, while at lethal 1387 nM that led to release of other ions (K, Zn) from the cells, La filled most of the cells. La had no clear positive effects on growth or photosynthetic parameters, but increasing concentrations led to a dramatic decrease in cell counts. Chlorophyll fluorescence kinetic measurements showed that La led to the inhibition of photosynthesis. Maximal photochemical quantum yield of the PSII reaction center in dark-adapted state (Fv/Fm) decreased at > 4.3 nM La during the 2nd week of treatment. Minimum dark-adapted fluorescence quantum yield (F0) increased at > 13.5 nM La during the 2nd week of treatment except for control (0.2 nM La, baseline from chemicals) and 0.3 nM La. NPQ at the beginning of the actinic light phase showed significant increase for all the treatments. Metalloproteomics by HPLC-ICPMS showed that La binds to a >500 kDa soluble protein complex already in the sub-nM range of La treatments, in the low nM range to a small-sized (3 kDa) soluble peptide, and at >100 nM La additionally binds to a 1.5 kDa ligand.
Keywords: fluorescence; fotosyntéza; listy rostlin; Lanthanum; Plant Leaves; chemické látky znečišťující vodu; Chlorophyta; Fluorescence; fotosystém II (proteinový komplex); Photosystem II Protein Complex; chlorofyl; Water Pollutants, Chemical; lanthan; Photosynthesis; Chlorophyll